Genre differentiation of Agatha Christie’s short stories - Zhanarka Ibrayeva; Gibadat Orynkhanova; Zhanar Zhardamaliyeva; Gulmira Karimova; Zhaina Kassymova (Progress in Science, 2025)
The detective genre is one of the most popular and widely read in the modern world. The main elements of the detective story are intricate plots, investigations and intrigues, which attracts readers of different ages. Relevance of the research: the study of the detective as a genre is researched insufficiently in modern society and is in its formative stage. The aim of the study is to analyse the popular works of the detective genre by Agatha Christie, to identify the main types of characters in her novels, determine the characteristic features of the author’s style in the works, and consider the subgenres of the author’s detective works. The study included following methods: synthesis, analogy, deduction, comparative, functional, logical and system analysis. The paper describes the main types of the classic detective, identifies the features of the classic detective, names 12 common genres of popular literature among readers, and analyses 145 works by the writer Agatha Christie, characterising the main characters that belong to 8 popular genres of detective stories, such as: detective, the story of confrontation, adventure story, mysterious story, a mystical story, melodrama, thriller, and quest. This study examines action-packed literature, which is part of a common cultural tradition together with works of “high” and “elitist” literature. A distinctive feature of action-packed literature is its is its genre-based canon and stereotypicality. Among the most controversial issues relating to the study of this type of literature is the problem of genre stratification. The practical value of the obtained results is expressed in the creation of a classification of the works of Agatha Christie, which can be used in literary studies.